Exploring how the experiences of English youth football coaches have shaped their approach to player learning - Jewell, S.; Murphy, C. P.; Pocock, C.; North, J. S. (The Journal of Sport and Exercise Science, 2022)
Recently the Football Association (FA) has highlighted a need to move away from traditional approaches to player learning through the dissemination of contemporary pedagogical research. Researchers have attempted to evaluate this process by investigating the practice activities engaged in by youth football teams; however, there remains limited understanding of why coaches adopt certain approaches to player learning. By acquiring youth football coaches` insights, this study addressed this gap by giving coaches a platform to share their approaches to player learning and the different experiences that have shaped it. Eight English youth football coaches (minimum FA Level 2 coaching qualification) were interviewed. Using inductive thematic analysis, eight higher order themes were identified and organised into three dimensions: (i) approaches to player learning, (ii) the coaching environment, and (iii) opportunities for learning and development. Despite some contemporary skill acquisition principles being evident in player learning approaches, coaches` understanding of how specific practice activities impact player learning outcomes was somewhat limited. Learning approaches themselves were not static, but dynamic and adaptable depending on social and contextual factors within the coaching environment. Similarly, these approaches were informed by a multitude of formal and informal learning opportunities, not solely formal coach education pathways. Together, the findings present a challenge for coach educators to account for the individual requirements of coaches and highlight the need to disseminate contemporary pedagogical principles in an easily digestible, transferable, and practical manner.